„Toruńskie Studia Bibliologiczne”. Formuła wydawnicza – profil – perspektywy - Ciszewska, Wanda A.; Kowalska, Małgorzata (Acta Universitatis Lodziensis. Folia Librorum, 2013)
Since 2008, the staff of the Institute of Scientific Information and Book Studies at Nicolaus Copernicus University in Torun established the scientific journal entitled “Bibliological Studies of Torun”. The basic idea of this periodical is publication of works that represent different disciplines of library and information science. Another role is to serve the wide LIS community and provide a platform for presentation of scientific achievements as well as a forum for exchange of experiences and discussion. The following paper presents brief information about the editorial staff, co-workers, publishing features and subject areas covered by “Bibliological Studies of Torun” between 2008 and 2012.